Methicillin-resistant Staphylococcus aureus with reduced vancomycin susceptibility in Taiwan - Chien-Yu Lin; Jui-Hsing Wang; Kai-Hsiang Lin; Yu-Ling Ho; Cheng-Mao Ho (Tzu Chi Medical Journal)
Staphylococcus aureus is a versatile pathogen which can cause various mild to life-threatening infectious diseases. The evolution of S. aureus resistance is notorious, from penicillin and oxacillin to vancomycin. Vancomycin, introduced in 1956, was once considered a most reliable antibiotic for methicillin-resistant S. aureus (MRSA); unfortunately, the first strain of S. aureus with decreased susceptibility to vancomycin emerged in 1996. Vancomycin has been approved in Taiwan since 1983, and the prevalence rates of heteroresistant vancomycin-intermediate S. aureus (hVISA) and vancomycin-intermediate S. aureus (VISA) in 2003 were 0.7% and 0.2%, respectively. However, a ten-fold increase of hVISA and VISA to 10% and 2.7%, respectively, in 2012–2013 could indicate a challenging clinical situation in Taiwan. The most commonly reported staphylococcal cassette chromosome mec (SCCmec) types of hVISA and VISA are usually SCCmec type III or II, typical nosocomial MRSA strains. Preventing the spread of resistant pathogens through infection control interventions and judicious antibiotic stewardship is a serious medical issue.